2020
DOI: 10.3390/nu12123759
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome, Aging, and Longevity: A Systematic Review

Abstract: Aging is determined by complex interactions among genetic and environmental factors. Increasing evidence suggests that the gut microbiome lies at the core of many age-associated changes, including immune system dysregulation and susceptibility to diseases. The gut microbiota undergoes extensive changes across the lifespan, and age-related processes may influence the gut microbiota and its related metabolic alterations. The aim of this systematic review was to summarize the current literature on aging-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(208 citation statements)
references
References 90 publications
9
167
2
1
Order By: Relevance
“…On the other hand, similar to the findings of Hoffman et al [ 36 ], we reported a distinction between rats at different ages, i.e., the older rats (15-week-old) had higher alpha diversity than young rats (10-week-old). Aging has physiological effects on both the host and the microbiome, and age-related processes may influence the gut microbiota and its metabolites [ 37 ]. Therefore, age should be considered when comparing the results containing age-dependent changes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, similar to the findings of Hoffman et al [ 36 ], we reported a distinction between rats at different ages, i.e., the older rats (15-week-old) had higher alpha diversity than young rats (10-week-old). Aging has physiological effects on both the host and the microbiome, and age-related processes may influence the gut microbiota and its metabolites [ 37 ]. Therefore, age should be considered when comparing the results containing age-dependent changes.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, recent interventional studies show probiotic administration of L. plantarum to fortify mucosal integrity [60] and improve exercise performance (i.e., grip strength and swim endurance) with age [61]. Moreover, a recent systematic review underscored the greater abundance of L. plantarum in healthy long-lived individuals [146], speculatively highlighting the importance of L. plantarum preservation throughout aging. In sum, these studies [54][55][56][57][58][59][60][61]146] provide compelling evidence in support of a role for the gut microbiome, and specifically L. plantarum, in influencing the somatotropic axis and thus, skeletal muscle responsiveness.…”
Section: Anabolic Hormone Responsesmentioning
confidence: 99%
“…Inter-individual differences in gut microbiota composition also tend to be emphasized in the older age, as suggested by a recent systematic review and meta-analysis of 27 human studies [13]. Resilience to stressors remains an important characteristic of the gut microbiota even in the late life.…”
Section: Physiological Effects Of Aging 21 the Aging Gut Microbiotamentioning
confidence: 96%